A systematic review and meta-analysis of neurotrophic tyrosine receptor kinase gene fusion frequencies in solid tumors. (December 2020) - Forsythe, Anna; Zhang, Wei; Phillip Strauss, Uwe; Fellous, Marc; Korei, Maesumeh; Keating, Karen
Introduction: The research objective was to systematically review evidence on neurotrophic tyrosine receptor kinase ( NTRK ) gene fusion frequency in solid tumors. Methods: Using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a systematic literature review (SLR) was conducted of studies published from January 1987 to 2 January 2020. Selected studies were appraised for use in meta-analysis, with frequency reported as a point estimate with confidence intervals, to estimate NTRK gene fusion tumor incidence and prevalence. Results: The SLR identified 222 studies from North America ( n = 122), Europe ( n = 33), Asia ( n = 41), Brazil ( n = 5), Australia ( n = 2), and multi-continental ( n = 19) reporting NTRK gene fusion frequencies across 101 histologies. Studies were prospective ( n = 43) and retrospective ( n = 179). Testing methods involved DNA ( n = 93), RNA ( n = 72), combined DNA/RNA ( n = 48), protein [immunohistochemistry (IHC), n = 5], and unreported ( n = 5). Sample sizes ranged from 1 to 66, 871. Of the 222 studies, 107 were suitable for meta-analysis. Highest NTRK gene fusion frequencies were reported in rare cancers: infantile/congenital fibrosarcoma (90.56%, 95% CI 67.42–100.00), secretory breast cancer (92.87%, 95% CI 72.62–100.00), and congenital mesoblastic nephroma (21.52%, 95% CI 13.06–32.20). Lower frequencies were reported in non-small cell lung cancer (0.17%, 95% CI 0.09–0.25), colorectal adenocarcinoma (0.26%, 95% CI 0.15–0.36), cutaneous melanoma (0.31%, 95% CI 0.07–0.55), and non-secretory breast carcinoma (0.60%, 95% CI 0.00–1.50). Reported frequency was 0% for some cancers: mesothelioma, renal cell carcinoma, prostate cancer, and bone sarcoma. Estimated global overall NTRK gene fusion tumour incidence and 5-year prevalence in 2018 was 0.52 and 1.52 per 100, 000 persons, respectively. Conclusion: This research confirms the rarity and varying frequency of NTRK gene fusion across tumor types. Limitations included relatively low historic NTRK gene fusion testing and reporting, limited study samples for some cancers, and suboptimal molecular testing methods. In this rapidly developing area, gold-standard testing methods and companion diagnostics are needed to capture all NTRK gene fusions.